Magnetic Resonance Imaging in Spinal Dysraphism - Yüksel Pabuşçu; Cem Tayfun; Bahri Üstünsöz; M. Ali Yinanç; Taner Üçöz; Erkin Oğur (European Journal of Therapeutics, 1994)
Spinal Dysraphism is a term that contains a lot of congenital developmental anomalies. it causes serious neurologic signs such as weakness and paralysis of extremities, mixion and defecation incontinance with esthetic losses such as scoliosis, back mass, hair type hypertrichosis in median back area. in this study, the diagnostic value of MRI in spinal dysraphism of 38 patients is discussed. Not: Bu makale dergimizin 1993 yılı 2. sayısında yayınlanmıştır, ancak, baskı hatası nedeniyle bu sayıda yeniden yayınlanması uygun bulunmuştur. https://doi.org/10.58600/eurjther-199342-1100-x Note: This article was published in the 2nd issue of our journal in 1993, however, due to a printing error, it was deemed appropriate to republish it in this issue. https://doi.org/10.58600/eurjther-199342-1100-x